Research methodology enabling to determine study programmes ability to produce the librarians as educators - Grigas, Vincas (Qualitative and Quantitative Methods in Libraries; Vol 2 No 2 (2013): June 2013 Issue, 2017)
The report discusses the possibilities of researching study programmes used for preparing professional librarians. Its purpose was to test the research methodology, allowing determining whether study programmes used for preparing professional librarians produce the entirety of competencies necessary for librarians as educators. Research made use of components of three Lithuanian institutions of tertiary education that provide study programmes designed for preparing professional librarians. The research proved that the Standards for Proficiencies for Instruction Librarians and Coordinators coupled with factor analysis may be an appropriate method for the assessment of study programmes designed for training future professional librarians. This research is interesting in two aspects: a) it uses standards developed by the professional librarian community that define the entirety of competencies necessary for a librarian as an educator;  b) analysis of relevant data employed factor analysis and multidimensional statistical scaling, usually used to determine interdependencies between objects of study or, based on those interdependencies, to classify their attributes.